An Analysis on Students’ Difficulties in Reading Aloud at The Eight GradeStudents of MTs Negeri 2 Buol - Padanggi, Alfin J.; Otoluwa, Moon Hidayati; Mamu, Rahmawaty (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study analyzes the difficulties faced by eighth grade students at MTs Negeri 2 Buol in reading aloud. This research aims to identify challenges and provide insights into the difficulties students face in reading aloud. The study used qualitative methods, including observation and semi-structured interviews with students and English teachers. The results showed that the main difficulty students faced was lack of comprehension (79.16%), then followed by pronunciation difficulties (70.83%) then followed by slowing reading speed which was (62.5%), and finally anxiety at (54.16%). Pronunciation difficulties are also common, where students often focus too much on articulation and lack of vocabulary, leading to errors in word pronunciation. Lack of comprehension became a significant issue due to students' limited knowledge of what they read, which hindered their ability to present the material fluently. Lastly, anxiety plays an important role, with students experiencing excessive anxiety due to factors such as low self-confidence, fear of making mistakes, discomfort with their reading ability, and fear of being laughed at by peers if they make mistakes.